2019
DOI: 10.3390/ijerph16234806
|View full text |Cite
|
Sign up to set email alerts
|

Level of Burden and Health-Related Quality of Life in Caregivers of Palliative Care Patients

Abstract: The complexity of palliative care means that the emotional distress and burden that primary family caregivers suffer under can be particularly high. The objective of this study was to determine the level of burden endured by these primary family caregivers and to identify the variables that predict it in the caregiving relatives of people who require home-based palliative care. A descriptive-correlational cross-sectional study was conducted. Socio-demographic and clinical data were collected from caregivers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 64 publications
(91 reference statements)
8
44
1
9
Order By: Relevance
“…Caregiving burden was associated with higher PTG in the regression analysis, which was consistent with findings in caregivers of palliative care patients in Spain 33 and head and neck cancer patients in Ireland 34 . Theorists have suggested that stressors should be perceived as sufficiently life‐threatening to challenge people's assumptions about the reality and to elicit coping processes 31 .…”
Section: Discussionsupporting
confidence: 80%
“…Caregiving burden was associated with higher PTG in the regression analysis, which was consistent with findings in caregivers of palliative care patients in Spain 33 and head and neck cancer patients in Ireland 34 . Theorists have suggested that stressors should be perceived as sufficiently life‐threatening to challenge people's assumptions about the reality and to elicit coping processes 31 .…”
Section: Discussionsupporting
confidence: 80%
“…In contrary, recent findings have demonstrated that caregiving for cancer and dementia patients have been associated with post traumatic growth and improvement in family resilience [22]. Over time, family members facing persistent challenges from caregiving to these conditions were found to develop personal and relational transformation to grow out of adversity.…”
Section: Introductionmentioning
confidence: 91%
“…Over time, family members facing persistent challenges from caregiving to these conditions were found to develop personal and relational transformation to grow out of adversity. Post traumatic growth and family resilience have been associated with a reduction in the risk of depression, anxiety and stress [22]. The positive outcome can also be explained by the subjective nature of caregiver burden where IC may suffer from burden but value the experience as it contributed to their own self-enrichment [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For their part, family caregivers are subjected to constant stress, which in many cases is greater than that experienced by other informal caregivers, since the patient often presents severe and changing symptoms that require close, constant care and attention. Under these conditions, the physical health of the caregiver may be affected [11,12], with a consequent negative impact on their quality of life [13,14].…”
Section: Introductionmentioning
confidence: 99%